Development of a wet fine screen model integrating the effect of operating and design variables on screening performance - Mabote, Seipati (Department of Chemical Engineering, 2016)
Mineral processing is the process that involves liberation and beneficiation of valuable constituents of an ore. Several physical beneficiation processes exist and one such process is classification. Screens are classification devices sometimes used in the classification stage of closed grinding circuits to separate mill product into different size classes. Poor classification of particles results in reduced throughput, high power consumption and over - grinding. Most of the research on screening has been done in scalping applications or classification at relatively large cut sizes. There is limited work done on screening at feed sizes of minus 150 μm and there are no robust models for wet fine screening application for use in circuit simulation studies. The effect of feed flow rate, solids concentration and aperture size on wet fine screening performance was evaluated in this study. The range of values of the factors investigated were the feed rate (9, 13, 19, 25, 30 and 35 t/h), screen aperture size (45, 75, 106 and 150 μm) and solids content (30, 40, 50 and 60%). A pilot Derrick screen plant at Mintek in Johannesburg was used for the experiments on a UG2 and chromite ore blend. Screen undersize and oversize samples were collected for particle size distribution analysis and mass balance calculations. The samples collected were filtered, de - lumped and split down to masses ranging between 200 and 300 grams for wet screening using the Malvern MasterSizer particle analyser. The results were used to analyse the effect of the investigated factors on the wet fine screening performance. These results were used to develop a wet fine screening model. Results indicate that increased feed flow rate and solids concentration lead to finer cut sizes, reduced sharpness of separation and higher water recoveries to the oversize. An increase in aperture size increased the sharpness of separation and decreased the water recoveries to the oversize. The solids concentration appeared to have a higher effect on cut size than the feed flow rate. The highest cut size and sharpness of separation and lowest water recovery to oversize were attained at the lowest feed rate. The lowest solids concentration produced the best performance with regards to all partition curve properties. The cut size approached the aperture size at the lowest throughput and solids concentration for all aperture sizes. All the efficiency curves exhibited fish hooks at fine particle sizes with the fish hooks becoming more pronounced at higher feed flow rates and solids concentration and smaller aperture sizes. A wet fine screen model that includes multi component ores as well as changes in operating conditions was developed using the 2 - parameter Whiten screen model as a basis. The dimensional analysis approach was applied in developing the sub - models that relate the operating and design parameters to the Whiten model parameters. The dimensional analysis approach was further applied to develop the model that describes the fish hook effect for subsequent incorporation into the overall modified fine screen model. Generally, the modified model is capable of predicting the performance of the wet fine screen reasonably well with minor errors and accommodates for the data that exhibits the fish hook. The model also reduces the fitting process required in the original Whiten model.